PENGUATAN MORAL ANAK SD MELALUI SOSIALISASI ANTI-BULLYING DAN KOLABORASI KOMUNITAS, SEKOLAH, ORANG TUA - Chairul Bahri Mesgiyanto; Zikri Ulfiandi, Ihsan; Rinda Eka Mulyani (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This research aims to evaluate the effectiveness of anti-bullying socialization programs based on Islamic values implemented by human rights mobilization communities in Samarinda City. This program involves collaboration between schools, parents, and the community in preventing bullying and strengthening the morale of elementary school children. The methods used are mixed-methods, which include interviews, observations, questionnaires, and literature studies. The results of the study showed that after three months of program implementation, there was a 35% decrease in bullying incidents. A total of 75% of students reported an increased understanding of the impact of bullying, and 60% were able to identify bullying behaviors around them. In addition, parental participation in school activities increased from 45% to 78%, which indicates improved communication and better collaboration between schools and families. This program also succeeded in introducing Islamic values such as rahmah and ukhuwah in student interaction, which had a positive impact on strengthening their morals. These findings show that collaboration between schools, parents, and the community is very effective in shaping children's character and reducing bullying behavior, and underscores the importance of religion-based moral education in supporting children's character development. Keywords: Strengthening children's morals; Anti-Bulliying Socialization; Community, School and Parent Collaboration